Cadets’ Perception and Effectivity of Quiz-Based Maritime English Teaching in V-Class During Covid-19 Pandemic Time - Sri Sartini; Yudhanita Pertiwi; Yudhi Setiyantara; Itsar Hartadi (Ethical Lingua: Journal of Language Teaching and Literature, 2021)
Education across Indonesia has declared a lockdown temporarily due to Covid 19 pandemic. E-learning was forced to be conducted to fulfil the education objectives. Sekolah Tinggi Maritim Yogyakarta (STIMARYO) as one of academic institutions was impacted and had to search new alternatives for its academic delivery. Virtual class named as V-class as a Moodle-based platform was the way forward. This study was aimed to gain an effective information on cadets’ perception toward the implementation of V-class specifically on the use of Maritime English Quiz-based instruction. Further it aimed to find correlation between cadet’s perception on V-class and cadet’s final score on quiz. The respondents were 45 cadets of Nautical Science and Ship Machinery Departments of Academic year 2020/2021. Descriptive statistics and bivariate correlation test were performed to analyze the collected data. The study revealed that cadet’s perception on STIMARYO V-class through the quiz-based instruction in Maritime English was satisfying. Thus, it led them to be self-directed learners that affected their learning motivation. Although it was medium correlation of r =0,464, p=0,004, it proved that cadet’s perception contributes to their learning success. Eventhough some drawbacks were also existed, in pandemic situation, they were normal to occur.